KESEDIAAN UNTUK MEMBAYAR PRODUK AKRILIK PADA KONSUMEN LETTERPRESS - Ricky Bagus Thrisnady; Christina Christina (Jurnal Performa : Jurnal Manajemen dan Start-up Bisnis, 2022)
For more than 2 years running, Letterpress often gets problem in sale in which often occurs cancel payment on Letterpress consumers. The purpose of this research is to analyse there is or no different willingness to pay Letterpress consumers based on age, gender, education, and income factors. The population of this research is people who had ever contacted Letterpress either have ever bought or have never bought Letterpress product, with the total amount of 65 people. This research uses primary data type such as online survey that is distributed to social media. The researcher will use Likert scale in willingness measurement to pay, and nominal scale in socioeconomic status (SES) measurement that is, age, gender, education and income. Sampling technique that is used is non-probability sampling with saturated sample method. The researcher uses different test to test hypothesis in the research that consists of one way ANOVA and independent sample t-test with the help of IBM SPSS Statistics 26. The result in this research indicats that there is different willingness to pay significantly that occurs on Letterpress consumers based on the age, education, and income. While in gender type of factor, there is no significant difference that occur.